A new coinductive confluence proof for infinitary lambda calculus - Łukasz Czajka (Logical Methods in Computer Science, 2020)
We present a new and formal coinductive proof of confluence and normalisation of B\"ohm reduction in infinitary lambda calculus. The proof is simpler than previous proofs of this result. The technique of the proof is new, i.e., it is not merely a coinductive reformulation of any earlier proofs. We formalised the proof in the Coq proof assistant.